Design of a digital interactive configuration, flexible and inexpensive, for monitoring the movements of people in real time - Enrico Costa (SCIRES-IT : SCIentific RESearch and Information Technology, 2014)
We aim to introduce here the idea and the first results of a still ongoing research regarding the setup of a flexible and inexpensive digital interactive configuration, which has the goal of tracking the position and routes of a certain amount of subjects inside a medium or large closed space. The configuration appears to be adequate especially for the monitoring of museums spaces, exhibitions and showrooms.